The learning process requires collaboration - Hia, Ines Priskila; Salsa, Natali Gloria; Wijayanti, Lucia Wiwid (Proceedings of International Conference on Research in Education, 2025)
Learning is not only an individual process; it also requires the involvement of others. Collaboration is crucial for students to exchange ideas and help each other understand the material. The method used in this research is a literature review. Data and information were obtained from five journals and two books, which served as primary sources. Papers indicate that collaboration-based learning models, such as project-based learning (PBL), project-based learning (PjBL), Team-Assisted Individualization (TAI), and online collaboration, significantly improve students' collaboration skills. Improvements were seen in aspects of contribution, time management, problem-solving, cooperation, and investigation, with percentages consistently improving from the pre-cycle to the second cycle, according to the research cited. Collaboration has also been shown to develop critical thinking skills, creativity, social skills, and learning motivation. Teacher and parental support, and the use of digital technology, play a significant role in the success of collaborative learning. It can be concluded that learning is not only related to understanding the material, but also involves interaction and collaboration among students. Through collaborative learning, learners can learn from one another, appreciate differences, and collectively construct a deeper meaning of learning. With the support of digital technology, this approach can create an active, participatory learning environment relevant to the demands of 21st-century education.
Keywords: collaboration; digital technology; learning; problem-based learning; project-based learning